Penelitian Tindakan Kelas: Meningkatkan kemampuan teknik dasar shooting sepakbola melalui metode bagian - Hasrion; Sari, Merlina; Gazali, Novri (Edu Sportivo: Indonesian Journal of Physical Education, 2020)
The purpose of this study was to determine the improvement of the basic techniques of shooting football through the section method in SMA Negeri 1 Pangean District, Kuantan Singingi Regency. This research is a class action research. More specifically this research is collaborative classroom action research, namely collaboration between researchers and field practitioners (Teachers). This research consists of several cycles, each cycle through stages, action planning, action implementation, observation and reflection. The subjects of this study were all students of class XI IPS2 of SMA Negeri 1, Pangean Subdistrict, Kuantan Singingi Regency with a total of 29 people. This study uses learning tools and data collection instruments rubric performance football shooting capabilities. In measuring the completeness of students, researchers used the assessment guidelines from the National Education Assessment Center. Based on the results of research and discussion, it can be concluded that the application of the part method can improve the basic technical skills of shooting soccer students in class XI IPS2 of SMA Negeri 1, Pangean Subdistrict, Kuantan Singingi Regency. Based on the findings of this study, it is hoped that physical education teachers can make the method part of the solution in improving students' basic technical skills in sports, especially soccer.